Chemiluminescence measurements as an indicator of cumene hydroperoxide-induced lipid peroxidation in human erythrocytes - (:unkn) unknown (My University, 1990)
Erythrocyte (RBC) suspensions were incubated with 0.05-1 mM cumene hydroperoxide (CumOOH) and an aliquot was removed periodically to measure the extent of hemolysis and lipid peroxidation. Lipid peroxidation was monitored by measuring thiobarbituric acid reactive substance (TBARS) formation. Chemiluminescence measurements were carried out in a liquid scintillation analyzer in the single-photon count mode. Changes in the extent of hemolysis. TBARS formation and chemiluminescence were all potentiated by increasing the CumOOH concentration. Analysis of the time course of the changes suggested that chemiluminescence and TBARS formation took place prior to development of hemolysis. Butylated hydroxytoluene (BHT) prevented the peroxidative changes induced by CumOOH.
Keywords: Chemiluminescence; cumene hydroperoxide; erythrocyte; hemolysis; lipid peroxidation